Teaching Reading Comprehension in English through Vocabulary: A Demonstration of Some Strategies - Adegbite, Wale (2014)
The effective teaching of reading comprehension to children requires the development of certain skills (viz: perceptive, cognitive and linguistic skills). These skills can be focused on severally during teaching or, otherwise, they can be integrated. Current thinking in teaching reading comprehension, however, would seem to favour the latter, in view of the maximum input benefit which pupils can derive from it.